Textifood : Futurotextiles. - Baud-Berthier, Claire; Cunier, Manon; Pereira, Leïla; Puype, Karel (Oostkamp : Stichting Kunstboek, 2015)
Dione, Aissa ; Collet, Carole ; Vigo, Chiara ; Phung, Christine ; Crucq, Morgane ; Marabelle, Coralie ; Brunet, Elodie ; Design Percept ; Sandico, Ditta ; Dognin ; Paris, Egide ; Riem, Em ; Raisina, Eric ; Cass, Gary ; Franklin, Donna ; Levivier, Geneviève ; A+Z Design ; Edvard, Jonas ; von Forselles, Kristian ; Cibic, Matteo ; Maisons de Mode ; L'Herbe Rouge ; Gautier, Nina ; Orange Fiber ; Hallette, Sophie ; Raden, Tamiya ; Baldizzone, Tiziana ; Baldizzone, Gianni ; Breton, Virginie ; BBdor
boek